Health Problems of Nepalese Migrant Workers and Their Access to Healthcare Services in three countries of Middle East - Paneru, Damaru Prasad; Adhikari, Chiranjivi; Pandey, Raju; Bhatt, Bimala; Chalise, Manisha; Baidhya, Nirdesh; Paudel, Arati (Journal of Karnali Academy of Health Sciences, 2020)
Background: Migrants’ health is a global public health issue. Middle East countries are the major destination for abroad job among Nepalese workers. This study carried out to identify the health problems among migrant workers and their access to health care in Saudi Arabia, United Arab Emirates (UAE) and Qatar of Middle East.Methods: This was a cross-sectional study; carried out among 480 returnee migrant workers who have given consent for the study. Data were collected at Tribhuvan International Airport (October 2018) using pretested structured interview schedule after taking approval from Institutional Review Committee of Pokhara University. Data were analyzed using SPSS 20 version. Percentage, mean/median, standard deviation, Chi square test and logistic regression performed.Results: Majority of the returnee migrants workers were male (95.0%) and their mean age was 32.38±5.54 years. Almost ten percent of the participants suffered from at least one health problem during their stay in Middle East; among them, respiratory problems were common (35.6%). Almost all participants (99.6%) had health policy to take care of migrant workers and 93.5 percent participants had health insurance coverage. Female workers (AOR 4.34; CI: 1.54-12.19), and migrants who worked for additional benefits (AOR 2.17; CI: 1.11-4.25) had significantly higher prevalence of health problems than their counterparts (P